The Relationship Between Gender Diversity and Quality of Greenhouse Gas Emission Disclosure in Indonesian Islamic Bank - Dian Yuni Anggraeni (Journal of Islamic and South East Asian Finance and Accounting, 2023)
This study aims to examine how gender diversity in Sharia Supervisory Board (SSB) affect the quality of greenhouse gas (GHG) emissions disclosure. The sample of this study consists of 64 observations (14 Islamic banks in Indonesia) during 2015-2018. The analysis of this study is using regression analysis with unbalanced panel data. It was found that gender diversity in SSB has no significant effect on quality of GHG emissions disclosure in Indonesian Islamic banks. It is probably due to the women’s representation in SSB is low. It indicates that Indonesia still faces a large gap in the percentage of women serving on boards and in leadership positions compared to men. The result is also likely to occur because SSB is still focused on its duties and responsibilities in the operational activities of Islamic banks, for example regarding the approval of new products, overseeing whether the contract is under the sharia principles, and reviewing Islamic bank financial statements.